Customer voluntary performance: consumers as company partners in delivering services - Aditya Yudanegara (Jurnal Mantik, 2023)
Customer Voluntary Performance (CVP) involves customers enhancing service quality as promoters, coproducers, and consultants. This study, using 200 questionnaires from retail customers and Structural Equation Modeling, reexamines CVP's antecedents: global customer satisfaction, commitment, and perceived support. The results confirm seven out of twelve hypotheses. Customer commitment positively affects loyalty and cooperation but not participation. Customer satisfaction shows no significant relation to loyalty, cooperation, or participation. Perceived customer support positively influences cooperation and participation but not loyalty. Additionally, customer satisfaction positively relates to perceived support, and both satisfaction and support positively correlate with customer commitment